2005
DOI: 10.1111/j.1365-2885.2005.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of the β2‐adrenergic receptor agonist zilpaterol on the LPS‐induced production of TNF‐α in vitro and in vivo

Abstract: In this study the anti-inflammatory properties of zilpaterol, a beta2-adrenergic receptor (AR) agonist specifically developed as a growth promoter in cattle were investigated. Although zilpaterol has a different structure compared with the beta2-AR agonists known to date, it was noted that it was able to bind to both the beta2-AR (Ki = 1.1 x 10(-6)) and the beta1-AR (Ki = 1.0 x 10(-5)). Using lipopolysaccharide (LPS)-exposed U937 macrophages, the production of cyclic adenosine-3',5'-cyclic monophosphate (cAMP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…These reports suggest that HO-1 protein and its enzymatic products ameliorate inflammatory disease via anti-inflammatory effects. Izeboud et al (1999) and Verhoeckx et al (2005) have demonstrated that β 2 -AR agonists had the inhibition effects on the LPS-induced production of proinflammatory cytokines both in human U-937 cell line (monocytederived macrophages) and in rats. Liaw et al (2003) have revealed that β 2 -AR agonists suppressed TNF-α and NO production via iNOS in LPS treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…These reports suggest that HO-1 protein and its enzymatic products ameliorate inflammatory disease via anti-inflammatory effects. Izeboud et al (1999) and Verhoeckx et al (2005) have demonstrated that β 2 -AR agonists had the inhibition effects on the LPS-induced production of proinflammatory cytokines both in human U-937 cell line (monocytederived macrophages) and in rats. Liaw et al (2003) have revealed that β 2 -AR agonists suppressed TNF-α and NO production via iNOS in LPS treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…saline or 3 mg/kg LPS. In previous studies, we and others have shown that this procedure induces an acute generalized inflammatory response [22]. At t = 0, and after 2, 4, 8, and 24 h respectively, four animals from both the saline and the LPS groups were anesthetized (only four saline treated animals at t = 0), blood was collected from the orbital sinus, captured in 1.3 mL EDTA coated tubes (Sarstedt; Etten-Leur, The Netherlands) and put on ice until centrifugation (10′, 10,000 rpm at 4°C).…”
Section: Animal Experimentsmentioning
confidence: 98%
“…TNF-a is an inflammatory factor produced by most inflammatory cells stimulated by LPS [27,28]. It can induce more inflammatory factors, which play a key role in the occurrence and development of SIRS (Systemic Inflammatory Response Syndrome) [29,30].…”
Section: Discussionmentioning
confidence: 99%